2010
DOI: 10.1164/rccm.200911-1738oc
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Multicenter Study of Adrenal Function in Critically Ill Children

Abstract: Rationale-Adrenal insufficiency is a clinical condition associated with fluid-and catecholamine-resistant hypotension.Objectives-The objectives of this study were to determine the prevalence of adrenal insufficiency, risk factors and potential mechanisms for its development, and its association with clinically important outcomes in critically ill children.Correspondence and requests for reprints should be addressed to Kusum Menon, M.Sc., Pediatric Intensive Care Unit, Children's Hospital of Eastern Ontario, 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
82
1
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(100 citation statements)
references
References 44 publications
(79 reference statements)
9
82
1
8
Order By: Relevance
“…In this large, multicenter observational study in six Canadian PICUs, we found that the overall consent rate for pediatric critical care research was 80.2% which is higher than what has been previously reported in several studies [4,6,7,20]. Many pediatric critical care studies have, in fact, not reported the consent rate in their manuscripts [21,22] making it difficult for researchers to obtain this information.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…In this large, multicenter observational study in six Canadian PICUs, we found that the overall consent rate for pediatric critical care research was 80.2% which is higher than what has been previously reported in several studies [4,6,7,20]. Many pediatric critical care studies have, in fact, not reported the consent rate in their manuscripts [21,22] making it difficult for researchers to obtain this information.…”
Section: Discussionmentioning
confidence: 63%
“…When compared with parents of children admitted to the PICU for all other reasons, parents of children undergoing anticipated or minor surgery were more likely to consent whereas legal guardians of children undergoing cardiac surgery were less likely to provide consent for research. The lower consent rate of cardiac surgery patients is important as these patients comprise 20-40% of participants recruited into previous pediatric critical care research studies [6,7] and 50% of the participants in this study. It will be important for researchers using the cardiac surgery population to incorporate the lower consent rate into their sample size estimation, recruitment processes, and anticipated trial duration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Menon et al conducted a very comprehensive work of relative adrenal insufficiency in critically ill children (n=381), not necessarily in shock, in seven pediatric tertiary intensive care units in Canada, supporting the concept of relative adrenal insufficiency in critical conditions. 22 In 2011, the RE-SOLVE trial 23 examined children with severe sepsis who received corticosteroids and showed that disease progression was similar to those who did not receive them. The results (mortality, time using inotropes, mechanical ventilation time, organ failure resolution, changes in mortality score, and hospitalization) were similar in children who were treated with and without steroids.…”
mentioning
confidence: 99%